New ways of communication with universities libraries users’ - Castillo Díaz, Ana; Herrera Morillas, José Luis (Historia y Comunicación Social, 2014)
This work presents an analysis of the use of the Web 2.0 tools by Spanish university libraries (social networks, photographs and video platforms, blogs, …). These tools make easier the interaction with the libraries users and are implemented by the vast majority of universities. Due to its high level of use and its utility is advisable to carry out an analysis in order to establish a number of patterns useful to optimize the communication in these sites.